Penerapan Konsep Arsitektur Islam pada Bangunan Masjid-Masjid di Kota Kendari - Shahrul Husein; Rian Zulfiqal; La Pande Jurumai (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2023)
Islamic architecture embodies the harmony of man's interaction with his surroundings and his Creator while fusing human culture with the process of his self-servitude to God. Complex geometric linkages, a hierarchy of ornamental forms, and extremely rich symbolic connotations can all be found in Islamic architecture. Islamic architecture was developed from the idea of Islamic religious philosophy taken from the Quran, Hadith, Sunnah, Fiqh, and Muslim Scholars. Islamic architecture itself is inseparable from His place of worship which is very attached to Islam, namely the mosque building. The shape of the structure, the shape of the roof (dome), façade, minaret, where the muadzin proclaims the call to prayer, and decoration in the form of calligraphy are indications that the mosque itself has a very similar sense of the mass of the building. Therefore, the purpose of this study is to show how Islamic architecture has been applied to a large number of mosque structures. The concept of study is mainly during the mosque architecture building, namely the visible image of the mosque, mosque plan, mosque history, mosque architectural characteristics, application of rules to mosque architecture, transformation of the shape of the mosque, and how the shape of doors and windows in mosque buildings in the city of Kendari. This research uses data collection methods in this case such as by conducting observations, descriptive, and surveys on mosques in the city of Kendari.